Early polysensitization is associated with allergic multimorbidity in PARIS birth cohort infants. Issue 8 (21st September 2016) - Gabet, Stephan; Just, Jocelyne; Couderc, Rémy; Bousquet, Jean; Seta, Nathalie; Momas, Isabelle
Abstract: Background: Profiles of allergic sensitization are poorly documented in infancy. Relations between early sensitization and allergic morbidity need to be clarified. Methods: This study dealt with children involved in the Pollution and Asthma Risk: an Infant Study (PARIS), a population‐based prospective birth cohort. Allergic sensitization to twelve food and four inhalant allergens was assessed at 18 months and defined by a specific immunoglobulin E (IgE) level ≥0.35 kUA /l. Health data were collected by standardized questionnaires at 2 and 6 years. Early allergic profiles were identified by an unsupervised cluster analysis based on health data at 2 years and IgE measurements. Profiles were compared with regard to allergic morbidity and multimorbidity at 6 years. Results: Sensitization to any allergen concerned 13.6% of infants. By cluster analysis, 1525 infants were grouped into three profiles: 89.2% not or rarely sensitized (only 3.7% of sensitized), 9.2% mainly sensitized to one or few allergens (45.2% of monosensitized and 45.9% of paucisensitized ) and 1.6% all polysensitized . The prevalence of doctor‐diagnosed asthma, rhinitis, eczema, food allergy and multimorbidity at 2 years increased from profile one to profile three ( p ‐trend <0.001). At 6 years, symptoms of current asthma, rhinitis, eczema and multimorbidity were significantly more frequent in the last two profiles. Conclusions: This study highlights, as early as 18 months of age, three profiles of increasing severity with regard to allergic sensitization and diseases. These profiles also differ in terms of allergic morbidity at 6 years. Early sensitization can predict allergic multimorbidity in childhood, and in the case of early polysensitization, multimorbidity is more frequent as soon as infancy.